EFFICACY OF SELECTED BOTANICALS AND MICROBIAL AGENTS AS ECO-FRIENDLY PROTECTANTS AGAINST Fusarium verticillioides (Sacc.) NIRENBERG EAR-ROT DISEASE OF MAIZE, Zea mays L. (2013)
Fusarium verticillioides is a major fungal pathogen of maize causing rots in seed, root, stalk and ear; seedling blight and fumonisin mycotoxin contamination of grains. Use of chemicals is being discouraged due to its human and environmental health hazards. Information on eco-friendly control method against the pathogen is scanty. Therefore, the efficacies of selected botanicals and microbial agents as eco-friendly control against F. verticillioides were determined. Six Quality Protein Maize (QPM) varieties (ART/98/SW5, ART/98/SW4, ART/98/SW6, OBATANPA, ILE-1-OB, TZPB) and ACR/99/TZL (local check) were evaluated in the field to identify susceptible varieties used as seed treatments in two planting seasons in Randomised Complete Block Design (RCBD) with three replicates. Seedling Blight (SB), Lodging after Tasselling (LT) and percentage ear-rot at maturity were assessed using standard procedures. Aqueous extracts of Tithonia diversifolia, Mirabilis jalapa, Senna occidentalis and Physalis angulata were evaluated in the laboratory in Completely Randomised Design (CRD) and on field in RCBD for fungicidal activities against F. verticillioides at 30.0%, 25.0%, 20.0%, 15.0%, 10.0% and 5.0% (w/v). Four microbial agents: Trichoderma pseudokoningii, T. harzianum, Pseudomonas fluorescens and Bacillus subtillis were separately bioassayed at four levels of concentration, alongside carbamate in the laboratory in CRD and the effective levels of concentration were used on the field in RCBD as protectants against F.verticillioides. ILE-1-OB, ART/98/SW5 and ACR/99/TZL seeds were treated with S.occidentalis at 10.0% and T. pseudokoningii at 7.1 x 108 spores/mL using three coating methods [Cooked-cassava Starch Slurry (CSS), Water Suspension (WS) and Powder Treatment (PT)] were used alongside carbamate (0.5 g/L). Data were taken on mycelial growth inhibition (%), germination (%) and yield (kg), and subjected to descriptive statistics and ANOVA at p=0.05. Variety ART/98/SW5 with 15.0% ear-rot; 13.0% SB and 18.0% LT was rated highly resistant. Other five varieties had >30.0% LT; >20.0% ear-rot and SB, rated moderately susceptible. Aqueous S. occidentalis at 10.0% caused most significant mycelial growth inhibition (20.1%) followed by M. jalapa (16.7%) at 25% concentration. Inhibitory property of S. occidentalis produced 3.1% yield increase compared with control. Conversely, T. diversifolia stimulated rather than inhibit mycelial growth of F.verticillioides by 1.9% at 25.0% concentration resulting in yield reduction by 1.4%. Similarly, P. fluorescens at 1.0x109 cfu/mL significantly inhibited mycelial growth by 51.8% followed by T. pseudokoningii at 7.1x108 spores/mL by 44.7%; which indicates high inhibitory potential against F.verticillioides in the field. Carbamate inhibited mycelia by 34.6% and 10.0% yield increase. Most effective coating method was CSS with significantly lowest incidence of ear-rot (15.0%) after carbamate (3.2%) followed by WS (20%) and PT (30%). Trichoderma pseudokoningii as microbial agent had highest effect (18.0%) on maize germination followed by (15.3%) P. fluorescens, (13.3%) T. harzianum and (1.6%) B. subtilis. Senna occidentalis and M. jalapa had significant effect of 11.1% and 8.3% respectively on maize germination compared with control, while T. diversifolia 3.0% and P. angulata 0.9%. Use of resistant variety-ART/98/SW5, aqueous extract of Senna occidentalis at 10.0% concentration and Trichoderma pseudokoningii at 7.1x108 spores/mL provided best treatment of Fusarium verticillioides of ear-rot disease of quality protein maize. These treatments could be incorporated into integrated management of the pathogen.